A Phase Ib Study of NUC‐1031 in Combination with Cisplatin for the First‐Line Treatment of Patients with Advanced Biliary Tract Cancer (ABC‐08). (3rd December 2020) - McNamara, Mairéad G.; Bridgewater, John; Palmer, Daniel H.; Faluyi, Olusola; Wasan, Harpreet; Patel, Alkesh; Ryder, William D.; Barber, Safia; Gnanaranjan, Chathunissa; Ghazaly, Essam; Evans, T.R. Jeff; Valle, Juan W.
Abstract: Background: Cisplatin/gemcitabine is standard first‐line treatment for patients with advanced biliary tract cancer (ABC). NUC‐1031 (phosphoramidate transformation of gemcitabine) is designed to enhance efficacy by maximizing intratumoral active metabolites. Methods: Patients with untreated ABC, Eastern Cooperative Oncology Group performance status 0–1 received NUC‐1031 (625 or 725 mg/m 2 ) and cisplatin (25 mg/m 2 ) on days 1 and 8, every 21 days. Primary objectives were safety and maximum tolerated dose; secondary objectives were objective response rate (ORR), pharmacokinetics, progression‐free survival (PFS), and overall survival (OS). Results: Twenty‐one patients (median age 61 years, n = 13 male; 17 cholangiocarcinoma, 2 ampullary, and 2 gallbladder cancer) received NUC‐1031 625 mg/m 2 ( n = 8 and expansion n = 7; median six cycles) or 725 mg/m 2 ( n = 6; median 7.5 cycles). Treatment was well tolerated; most common treatment‐emergent grade 3–4 adverse events occurring in more than one patient with 625 mg/m 2 NUC‐1031 were increased gamma‐glutamyl transferase (GGT), 40%; alanine aminotransferase, 20%; bilirubin, 13%; neutropenia, 27%; decreased white cell count, 20%; thrombocytopenia, 13%; nausea, 13%; diarrhea, 13%; fatigue, 13%; and thrombus, 20% and with 725 mg/m 2, increased GGT, 67%, and fatigue, 33%. NUC‐1031 725 mg/m 2 was selected as the recommended dose with cisplatin in ABC. ORR was 33% (one complete response, six partial responses), DCR was 76%, median PFS was 7.2 months (95% confidence interval [CI], 4.3–10.1), and median OS was 9.6 months (95% CI, 6.7–13.1). The median estimates of area under the plasma concentration–time curve from time 0 to last measurable time and maximum concentration were highest for NUC‐1031 (218–324 μgh/mL and 309–889 μg/mL, respectively) and lowest for di‐fluoro‐deoxycytidine (0.47–1.56 μgh/mL and 0.284–0.522 μg/mL, respectively). Conclusion: This is the first study reporting on the combination of NUC‐1031 with cisplatin in ABC and demonstrated a favorable safety profile; 725 mg/m 2 NUC‐1031 in combination with cisplatin is undergoing phase III trial evaluation in ABC. (ClinicalTrials.gov ID: NCT02351765; EudraCT ID: 2015‐000100‐26). Implications for Practice: The prognosis for patients with advanced biliary tract cancer (ABC) is approximately 1 year, and new treatment options are required. The cisplatin/gemcitabine combination is standard first‐line treatment for patients with ABC. NUC‐1031 is a phosphoramidate transformation of gemcitabine and is designed to enhance efficacy by maximizing intratumoral active metabolites. This phase Ib study (ABC‐08) demonstrated a favorable safety profile of NUC‐1031 in combination with cisplatin for the first‐line treatment of patients with ABC, and 725 mg/m 2 NUC‐1031 was recommended in combination with cisplatin for phase III trial evaluation; the NuTide:121 global randomized study is currently enrolling. Abstract : Standard of care for patients with advanced biliary tract cancer is combination therapy with cisplatin and gemcitabine. New therapeutic options are needed. This article assesses the safety of NUC‐1031 in combination with cisplatin and evaluates its antitumor activity in patients with advanced biliary tract cancer.